2013
DOI: 10.1128/jb.00818-13
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of SbmA, a Bacterial Inner Membrane Transporter Required for Importing the Antimicrobial Peptide Bac7(1-35)

Abstract: SbmA is an inner membrane protein of Gram-negative bacteria that is involved in the internalization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
102
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 38 publications
7
102
0
Order By: Relevance
“…Our results show that the sbmA gene can be efficiently expressed in P. aeruginosa, resulting in functional transport, and confirm that the SbmA protein is a stand-alone transporter that does not need other subunits to translocate proline-rich peptides across the membrane (29).…”
Section: Mode Of Action Of Bac7(1-35) Against P Aeruginosamentioning
confidence: 56%
See 1 more Smart Citation
“…Our results show that the sbmA gene can be efficiently expressed in P. aeruginosa, resulting in functional transport, and confirm that the SbmA protein is a stand-alone transporter that does not need other subunits to translocate proline-rich peptides across the membrane (29).…”
Section: Mode Of Action Of Bac7(1-35) Against P Aeruginosamentioning
confidence: 56%
“…The mechanism of action of PR-AMPs, such as Bac7 and other proline-rich peptides, has previously been well depicted in E. coli and Salmonella enterica serovar Typhimurium (22,28). PR-AMPs cross the plasma membrane, exploiting the inner membrane protein SbmA (23,29), and enter the cytoplasm, where they inhibit vital functions such as protein synthesis (12). Bac7(1-35) and other PR-AMPs have also shown membranolytic activity in E. coli and S. Typhimurium, but only at much higher concentrations than their MIC values (16-to 64-fold); however, lytic effects due to PR-AMPs occur over longer times than those observed by most AMPs with lytic activity (30).…”
Section: Mode Of Action Of Bac7(1-35) Against P Aeruginosamentioning
confidence: 99%
“…Since the genes are under the same operon, production and export from the cell are very efficient and toxic levels of MccJ25 are prevented from building up. Inside the target cell (Runti et al , 2013; Mathavan et al , 2014), MccJ25 inhibits the bacterial RNA polymerase (Semenova et al , 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Initial bioinformatic analyses of the SbmA amino acid sequence allowed classification of the protein as a transmembrane domain (TMD), part of an ABC (ATP-binding cassette) transporter that would require a yetunidentified nucleotide binding domain (NBD) to be fully functional (5). Nevertheless, Runti et al, in the accompanying article (17), did not find any putative NBD partner in Escherichia coli for SbmA and showed that SbmA-mediated transport of Bac-7 requires the transmembrane electrochemical proton gradient and that it is independent of ATP hydrolysis.…”
mentioning
confidence: 99%
“…This observation is in agreement with an SbmA model having 8 TM domains. In addition, Runti et al (17) by means of a two-hybrid assay showed that SbmA forms homodimers and provided indirect evidence that both C and N termini of SbmA are orientated to the cytoplasm.…”
mentioning
confidence: 99%